Elevated homocysteine levels predict impaired liver and renal function in women of reproductive age with polycystic ovary syndrome: a post-hoc analysis of a randomized controlled trial - Luo, Xi; Cai, Wang-Yu; Wu, Xiao-Ke (Frontiers in Nutrition, 2026)
BackgroundPolycystic ovary syndrome (PCOS) is associated with liver and kidney injury. Homocysteine (Hcy) may serve as a link between liver/kidney health and PCOS. This research aims to evaluate the relationship between serum Hcy levels and indicators of liver and renal function in women of reproductive age with PCOS.MethodsA post-hoc analysis of a randomized controlled trial is performed in this study. A total of 1,000 women diagnosed with PCOS were enrolled from secondary and tertiary hospitals in China. At baseline, we collected demographic information and measured metabolic factors, sex hormone levels, liver and renal function parameters, and Hcy levels. Women with an Hcy level >15 μmol/L were diagnosed with hyperhomocysteinemia (HHcy). Parameters associated with liver function were aspartate transferase (AST), alanine transferase (ALT), bilirubin, and total bile acid, while indicators of renal function were blood urea nitrogen (BUN), creatinine (CREA), cystatin C, and β2 microglobulin. Additionally, renal function was assessed using the glomerular filtration rate (eGFR).ResultsOf the 938 PCOS women with available data, 149 (15.9%) were diagnosed with HHcy, while 789 (84.1%) had normal Hcy levels. Compared to the normal Hcy group, the HHcy group exhibited increased levels of AST (12.5 vs. 15.7, p < 0.001), ALT (8.7 vs. 10.3, p = 0.041), indirect bilirubin (4.2 vs. 4.7, p = 0.013), CREA (41.8 vs. 48.7, p < 0.001), BUN (4.3 vs. 4.7, p < 0.001), β2 microglobulin (1.3 vs. 1.5, p < 0.001), and cystatin C (0.4 vs. 0.6, p < 0.001) levels, along with a lower eGFR (120.9 vs. 127.7, p < 0.001). The levels of AST, ALT, CREA, and BUN were found to be significantly increased in all Hcy quartiles, while eGFR was decreased across Hcy quartiles (P for trend <0.05). After adjusting for BMI, waist circumference, glucose, TC, and HDL, Hcy levels were positively associated with AST (β = 0.268, p < 0.001), total bilirubin (β = 0.127, p < 0.001), direct bilirubin (β = 0.038, p = 0.002), indirect bilirubin (β = 0.087, p < 0.001), total bile acid (β = 0.051, p = 0.015), CREA (β = 0.812, p < 0.001), BUN (β = 0.051, p < 0.001), β2 microglobulin (β = 0.026, p < 0.001), cystatin C (β = 0.013, p < 0.001), and eGFR (β = −0.810, p < 0.001); however, there was no association betweenHcy levels and ALT (β = 0.051, p = 0.381) after adjusting for confounding factors.ConclusionElevated Hcy levels are significantly associated with indicators of impaired liver and renal function in women of reproductive age with PCOS.